Penolakan Radikalisme Agama melalui Idiom Palembang - Zuhdiyah, Zuhdiyah; Hamzah, Amir (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to describe the forms of Palembang language idioms that are still used by the community and map the forms of community resistance to religious radicalism. This type of research is descriptive qualitative. The informants in this research were Palembang speakers in the Seberang Ulu and Seberang Ilir areas who were selected based on predetermined criteria. The research process started from desk-review, field observation, documentation, in-depth interviews and FGD. Data analysis in this research uses data reduction, presentation and drawing conclusions. The results obtained from the research are that there are 158 Palembang idioms that are still used by the public, and there are 10 idioms that are appropriate for resisting radicalization, namely: (1) Ado gawe, (2) Balak duobelas, (3) Besak kelakar, (4) Katek aguk, (5) Katek antanan, (6) Makan olo'an, (7) Ngeci'ke bala', (8) Pakem tuo, (9) Tempuan tahlil, (10) Wong kito galo. Rejection of destructive-anarchist actions both towards adherents of other religions and those of their own religion. This study illustrates the need for these idioms to be disseminated to the public and taught in schools. Further research needs to be carried out to fully understand how idioms can influence children's thoughts and behavior through experimental studies. Discussion and other limitations will be explained in this paper.